Innovation Social Processing Waste Skin Siamese Orange Becomes Plastic Raw Materials Biodegradable Named OraPlast - Rama Sanjaya; Catherine Wahyuning Wilujeng; Azrah Andriani (ENVIBILITY: Journal of Environmental and Sustainability Studies, 2025)
Air Talas Village in Muara Enim Regency, South Sumatra, is known as a center for cultivating Siamese oranges. This agricultural activity produces large amounts of orange peel waste every harvest season. Amidst these challenges, innovation in waste utilization is the key to sustainable solutions. PT Pertamina EP Limau Field together with the Air Talas Village community launched the Gema Dewata program. Social innovation in this program is found in the sub-program, namely Paklek Manis (Siamese Orange Peel Waste Processing), which aims to convert orange peel waste into raw materials for biodegradable plastic, called OraPlast. This research uses the PAR (Participatory Action Research) research method. The novelty of this innovation lies in the utilization of organic orange peel waste as a solution for environmentally friendly pectin-based biodegradable plastic. The utilization of orange peel waste of 34.79 tons/year which was previously discarded and produced 36,525 tons of CO2eq/year was intervened through the OraPlast innovation to be utilized as much as 30% or as much as 10.4 tons/year so that it can reduce the potential for GHG (Greenhouse Gas) emissions produced by 10,957.50 tons of CO2eq. In addition, the Amerta group that manages this innovation is able to generate income of IDR 4,200,000/month. The total direct beneficiaries are 213 people and 1090 indirect beneficiaries. The benefits of this program are very broad, ranging from reducing the amount of organic waste in the environment, creating new business opportunities, to providing an alternative to biodegradable plastic. With the right development, OraPlast has the potential to become a superior regional product that can compete nationally and even internationally as a solution to replace conventional plastic that is difficult to decompose.